Study on the impact of time delay to power system small signal stability - Jia, H.; Na Guangyu; Lee, S.T.; Pei Zhang (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
The impact of time delay on power system small signal stability is investigated in this paper. Theory on dynamic system stability with time delay is first briefly reviewed. Then, a single-machine-infinite-bus system is employed to analyze the impact of time delay on the system small signal stability analysis. It is found that when the delay is small, it can be ignored. However, if the delay is large, it can significantly change the system dynamic characteristics, such as the oscillation mode and the system critical eigenvalues. Studies of this paper are helpful to appropriately consider the effect of time delay in power system controller design and small signal stability studies